Приховане буття, або криза Української республіканської капели - Калуцка, Н. (Студії мистецтвознавчі, 2007)
In the proposed article the author is talking about the history of the Ukrainian Republican Cappella in its most painful time – crisis of its “European” period. The impossibility to return to Ukraine was one of the most tragic emotions of the artistic life of O. Koshyts.